Recurrent Rhabdomyolysis in a Medical Cadet during Military Training as a Rare Initial Presentation in Calpainopathy - Sethapong Lertsakulbunlue; Boonsub Sakboonyarat; Piradee Suwanpakdee; Boonchai Boonyawat (Case Reports in Neurological Medicine)
Rhabdomyolysis, an emergency medical condition linked to muscle necrosis and intracellular substances released into the bloodstream, significantly endangers military personnel in heat-stress conditions. Rhabdomyolysis can also be an initial presentation in inherited muscle disorders. This study reports a novel case of calpainopathy (LGMDR1) diagnosed in a 19-year-old male military cadet who initially presented with recurrent rhabdomyolysis during training, a rare presentation in LGMD patients. Furthermore, a persistent creatine kinase (CK) elevation was observed at baseline. The diagnosis was confirmed by identifying a compound heterozygous of a novel frameshift, c.606dup (p.Ala203CysfsTer9), a mutation in exon 4, and a missense, c.956C > T (p.Pro319Leu), a mutation in exon 7 of the CAPN3 gene, via whole exome sequencing. This case highlights the necessity of diagnostic investigation in individuals who have persistent high CK levels during the rhabdomyolysis episodes and possibly CK screening prior to military training to preemptively identify and mitigate complications from undiagnosed muscular dystrophies in military personnel in the future.